Sowing depths of brachiaria in intercropping with corn in no tillage planting - Gazola,Rodolfo de N. (2013)
The forage production in crop-livestock integration is critical both for formation of straw for no tillage planting and food for livestock farm. The experiment was conducted in the autumn/winter of 2009 and 2010, in the city of Selvíria -state of Mato Grosso do Sul -MS, Brazil, at Experimental Station of FEIS/UNESP. The objective was to evaluate the optimal depth for deposition of seeds of two Brachiaria species intercropped with corn with emphasis on grain yield and straw. The experimental design was a randomized block design in a factorial scheme 3 x 3, with four replications. The main treatments were two species of Brachiaria (Urochloa brizantha "Marandú" and Urochloa ruziziensis), which seeds were mixed with corn fertilizer and a control treatment (without intercropping). Secondary treatments consisted of three depths (8; 10 and 16 cm) in the deposition of fertilizer (in the consortium and the control treatments). The intercropping corn with Brachiaria produced similar amounts of straw. The straw total production was higher when intercropped and decreased with depth. The consortium with U. ruziziensis provided higher grain yield of corn in relation to U. brizantha, in 2010. The sowing depth of forages did not affect corn yield.